Classical light vs. nonclassical light: characterizations and interesting applications. Issue 2 (22nd January 2018) - Pathak, Anirban; Ghatak, Ajoy
Abstract: We briefly review the ideas that have shaped modern optics and have led to various applications of light ranging from spectroscopy to astrophysics, and street lights to quantum communication. The review is primarily focused on the modern applications of classical light and nonclassical light. Specific attention has been given to the applications of squeezed, antibunched, and entangled states of radiation field. Applications of Fock states (especially single photon states) in the field of quantum communication are also discussed.